Proteasome 26S subunit PSMD1 regulates breast cancer cell growth through p53 protein degradation. (3rd August 2017) - Okumura, Toshiyuki; Ikeda, Kazuhiro; Ujihira, Takafumi; Okamoto, Koji; Horie-Inoue, Kuniko; Takeda, Satoru; Inoue, Satoshi
Abstract: Endocrine therapy using antiestrogens and aromatase inhibitors is usually efficient to treat patients with hormone-sensitive breast cancer. Many patients with endocrine therapy, however, often acquire resistance. In the present study, we performed functional screening using short hairpin RNA library to dissect genes involved in antiestrogen tamoxifen resistance in MCF-7 breast cancer cells. We identified seven candidate genes that are associated with poor prognosis of breast cancer patients based on clinical dataset. The expression levels of six out of seven genes were higher in 4-hydroxytamoxifen (OHT) resistant MCF-7 (OHTR) cells compared with parental MCF-7 cells. Among the six selected genes, siRNA-mediated knockdown of PSMD1 and TSPAN12 markedly reduced the proliferation of OHTR cells. Notably, the knockdown of proteasome 26S subunit PSMD1 exhibited cell cycle arrest and the accumulation of p53 protein through inhibiting p53 protein degradation. In accordance with p53 accumulation, its target genes p21 and SFN were also upregulated by PSMD1 silencing. Taken together, PSMD1 was identified as a potential gene that plays a role in the development of tamoxifen resistance in breast cancer cells. These findings will provide a new insight for the mechanism underlying endocrine therapy resistance and a prognostic and therapeutic molecular target for advanced breast cancer.